2012
DOI: 10.1002/lnc3.366
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Substance in Artificial‐Phonology Learning, Part II: Substance

Abstract: Artificial analogues of natural-language phonological patterns can often be learned in the lab from small amounts of training or exposure. The difficulty of a featurallydefined pattern has been hypothesized to be affected by two main factors, its formal structure (the abstract logical relationships between the defining features) and its phonetic substance (the concrete phonetic interpretation of the pattern). This paper, the second of a two-part series, reviews the experimental literature on phonetic substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(116 citation statements)
references
References 72 publications
3
113
0
Order By: Relevance
“…It has been argued that phonological generalizations are easier to learn when they can be described using fewer features (e.g., Moreton & Pater, 2012). Because examples ending in voiced stops and voiceless fricatives were withheld from training, targeting a more general class of sounds would (a) be equally consistent with the input, (b) require fewer features for grouping the sounds, and (c) explain the extension to untrained sounds in the Potentially Saltatory condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been argued that phonological generalizations are easier to learn when they can be described using fewer features (e.g., Moreton & Pater, 2012). Because examples ending in voiced stops and voiceless fricatives were withheld from training, targeting a more general class of sounds would (a) be equally consistent with the input, (b) require fewer features for grouping the sounds, and (c) explain the extension to untrained sounds in the Potentially Saltatory condition.…”
Section: Discussionmentioning
confidence: 99%
“…Velar stops are more acoustically and perceptually similar to palato-alveolar affricates before high vowels than before mid vowels (e.g., [ki] and [tʃi] are more similar than where the alternating sounds were more similar to each other. With the support of a computational model, Wilson suggested that phonetic similarity was responsible for the observed asymmetry in degree of generalization (but see Moreton & Pater, 2012, for potential problems with the interpretation of these results).…”
Section: The Principle Of Minimal Modification As the Basis For A Leamentioning
confidence: 99%
See 1 more Smart Citation
“…One bias with ample support in the literature is that complex patterns are more difficult to learn, and less readily generalized, than simpler patterns (adults: Pycha et al, 2003;infants: Saffran & Thiessan, 2003;Cristia & Seidl, 2008;Chambers et al, 2011; for an overview see Moreton & Pater, 2012a). A more controversial proposal (see Moreton & Pater, 2012b) is that learners prefer patterns with an underlying phonetic motivation, sometimes called a substantive bias (e.g., Wilson, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Admittedly, how and when listeners generalize from a set of sounds used in the exposure to other sounds is an open topic -see e.g., Moreton and Pater (2012) for a recent review of artificial grammar learning work.…”
Section: Footnotesmentioning
confidence: 99%